Vernacularization: A Cross-Disciplinary Review - Tuuli Tahko; Jani Marjanen (Redescriptions)
Vernacularization is a term that many linguists, historians, anthropologists, and others have adopted to refer to changing linguistic, social, and cultural hierarchies within communities. While the phenomena described in these studies are certainly related, the actual meanings given to vernacularization vary so much as to include near opposites. In this article, we review the various uses of ‘vernacularization’ in the linguistic–historical context and delve into some of the more metaphorical usage of the term in neighbouring fields, discerning six interrelated strands of scholarly argumentation around vernacularization. We argue that increased awareness of the different characteristics assigned to vernacularization in these strands would improve its usefulness as an analytical concept across disciplines.